2018
DOI: 10.1002/adfm.201807034
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Anion on the Transport and Structure of Organic Mixed Conductors

Abstract: Organic mixed conductors are increasingly employed in electrochemical devices operating in aqueous solutions that leverage simultaneous transport of ions and electrons. Indeed, their mode of operation relies on changing their doping (oxidation) state by the migration of ions to compensate for electronic charges. Nevertheless, the structural and morphological changes that organic mixed conductors experience when ions and water penetrate the material are not fully understood. Through a combination of electrochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
195
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 135 publications
(225 citation statements)
references
References 70 publications
15
195
0
8
Order By: Relevance
“…Considering that the onset of oxidation potential is approaching to 0 V versus Ag/AgCl for the polymers with high EG content (Figure S4, Supporting Information), we expect that these polymers are already oxidized in the absence of an applied bias. Cendra et al showed that due to its low ionization potential, g‐100% can become oxidized by side reactions in ambient conditions . It might be also possible that the longer EG hydrophilic chains present in the 2g polymer chelate ions, contributing to the capacitance in the unbiased condition.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Considering that the onset of oxidation potential is approaching to 0 V versus Ag/AgCl for the polymers with high EG content (Figure S4, Supporting Information), we expect that these polymers are already oxidized in the absence of an applied bias. Cendra et al showed that due to its low ionization potential, g‐100% can become oxidized by side reactions in ambient conditions . It might be also possible that the longer EG hydrophilic chains present in the 2g polymer chelate ions, contributing to the capacitance in the unbiased condition.…”
Section: Resultsmentioning
confidence: 99%
“…Our results demonstrate that conjugated polymers operating in aqueous electrolytes experience significant changes in their structure and morphology during electrochemical doping. Previous work with p(g2T‐TT), i.e., g‐100%, evidenced that during doping, anions cause a lamellar expansion in the crystallites as they infiltrate and accumulate between the hydrophilic side chains . The majority of water uptake, on the other hand, occurs in the amorphous regions of the film .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations